Religion -Based School Management In Improving The Learning Process And Its Implications For Student Achievement (Survey Study At SMP Negeri 44 Bandung) - Muhammad Dadi Firdaus (Sean Institute, 2024)
Through this research, it is hoped that we will obtain empirical evidence regarding the implementation of religion-based school management in improving the learning process and its implications for student achievement . The object of this research is the students of SMPN 44 Bandung , because based on the researcher's observations, the phenomenon of stagnation occurs. learning process which has implications for low student achievement . The research method used is descriptive and descriptive analysis with data collection techniques using questionnaires distributed to students using Non-Random Sampling Techniques/Non-Probability Sampling/Non-Random Samples with Purposive Sampling type . . The total population was 866 people and the sample was 90 people. The results of the descriptive analysis proved that